Pengaruh Kepemilikan Institusional, Dewan Komisaris Independen dan Komite Audit Terhadap Penghindaran Pajak (Tax Avoidance) pada Perusahaan Perbankan yang Terdaftar di Bursa Efek Indonesia Periode 2012-2016 - Noor Mita Dewi (Universitas Muhammadiyah Semarang, 2019)
This study aims to predict empirical evidence regarding the effect of institutional ownership, independent boards and audit committees partially or simultaneously on tax avoidance in banking companies listed on the Indonesia Stock Exchange for the period 2012 - 2016. Based on this, this study takes the title